Frequencies of double- and multiple-break translocations in relation to radiation dose, and other genetical studies - Sidky, Abd El Razzak (The University of Edinburgh, 1939)
(1) The Frequencies of Double- and Multiple- Break Translocations in relation to Radiation Dose. (2) A Case of Gonosomic Mosaicism involving a Lethal. (3) Genetical Studies of the "Spheroidal" Mutant of Drosohila Funebris.
The frequencies of double- and multiple-break translocations in relation to radiation dose, and other genetical studies